IN PROMOTION OF INTEREST IN SPORTS ROLE - Kazakov A. R. (Web of Journals Publishing, 2025)
This article examines the role of educators in fostering interest in sports among young people, as well as the integration of physical education and sports into the educational process. The article outlines the educator's tasks and methodologies, including awakening interest in sports, promoting a healthy lifestyle and developing teamwork and psychological resilience. It also highlights the importance of using modern technologies and collaborating with parents in the promotion of sports. The article emphasizes the results of pedagogical work and the positive changes in students' lives related to their increased interest in sports and personal development.
Keywords: Educator, interest in sports, physical education, educational process, motivation, methodology, teamwork, psychology, modern technologies, collaboration with parents, healthy lifestyle, effectiveness of pedagogical work.